Influence of regioselectively sulfated cellulose on in Vitrovascularization of biomimetic bone matrices - Weber, Dominik; Andrulis, Mindaugas (Biomacromolecules, 2018)
ABSTRACT:Vascularization is essential for the regeneration of bone tissue within composite material. We measured the effectof regioselectively modified cellulose/hemicellulose as an additive for porous scaffolds of collagen/hydroxyapatitenanocomposite on the tubule formation of human vascular endothelial cells. Using a coculture of endothelial cells andfibroblasts, endothelial cells formed a network of tubules within an incubation time of 14 to 24 days. A cellulose sulfate withirregular sulfation pattern along the polysaccharide backbone (13-TACS-01) led to an additional increase in vascular endothelialgrowth factor (VEGF)-induced tubule formation, as observed in an in vitro angiogenesis assays. In contrast with structurallydifferent heparin, these cellulose sulfates have no apparent affinity to VEGF. Their impact on endothelial function may possiblybe due to interactions with cell surface receptors/soluble factors not yet defined.
Gesehen am 27.06.2019